Immunogenic potential of irradiated lymphoma cells is enhanced by adjuvant immunotherapy and modulation of local macrophage populations. Issue 9 (September 2013) - Honeychurch, Jamie; Melis, Monique H. M.; Dovedi, Simon J.; Mu, Lijun; Illidge, Timothy M.
Abstract: The aim of this study was to assess the immunogenic potential of irradiated lymphoma cells in vivo and determine whether immunogenicity can be enhanced by modulation of the host immune system. Syngeneic murine lymphoma models irradiated ex vivo were used as an orthotopic cellular vaccination prior to challenge with viable tumor cells. We demonstrate that irradiated lymphoma cells are poorly immunogenic and that protective anti-tumor CD8 T-cell responses require the addition of immunostimulatory monoclonal antibody as an immune adjuvant, and increased frequency of antigen exposure by multiple vaccinations. Furthermore, we show the potential importance of macrophages in regulating immunogenicity of irradiated lymphoma cells and demonstrate that depletion of macrophages using clodronate-encapsulated liposomes considerably enhances primary vaccination efficacy in the presence of adjuvant anti-CD40 antibody. Our results demonstrate that the immunogenic potential of poorly immunogenic lymphoma cells dying after radiation therapy can be improved by modulation of the host immune system.